The health risk of formaldehyde to human beings. - S., Norliana; Abdulamir, Ahmed Sahib; Abu Bakar, Fatimah; Salleh, Abu Bakar (Science Publications, 2009)
Problem statement: Formaldehyde was classified as a potential human carcinogen, identified by the US Environmental Protection Agency and International Agency for Research on Cancer as a Class 2A carcinogen. It also can cause irritation to human. However, formaldehyde present in biological fluids or tissues and environment as a result of natural processes or from man-made sources and can be emitted slowly into the air. Formaldehyde was used in many industries, hospitals and research as a sterilizing and preserving agent. The utmost concern of this study was about the present of formaldehyde in seafood product. Approach: A review was done on the health effect adverse by formaldehyde, formaldehyde toxicity to human, formaldehyde in seafood and methods to control formaldehyde in food and seafood. Google, Pubmed, Science Direct and Scopus were used in preparation of this review. Results: This review clarified that one of the formaldehyde source to human was seafood. Previous study showed that seafood contained high amount of formaldehyde because of natural production by postmortem enzymatic reaction besides the used of formaldehyde as preservative. Based on prior studies, exposure to formaldehyde can cause irritation and genotoxicity effect. For cancer effect studies, formaldehyde was long considered as a potential human carcinogen based on experimental animal studies and limited evidence of human carcinogenicity. Conclusion: Several mefinding of many health effect of formaldehyde, suggests that the investigation of level of formaldehyde in seafthods have been suggested to reduce formaldehyde in food such as cooking and washing. The ood should be done and also the level of formaldehyde natural production.